Prognostic factors for isolated medial patellofemoral ligament reconstruction: A systematic review - Migliorini, Filippo; Eschweiler, Jörg; Betsch, Marcel; Knobe, Matthias; Tingart, Markus; Maffulli, Nicola (Surgeon-Journal of the Royal Colleges of Surgeons of Edinburgh and Ireland, 2021)
Background: Evidence concerning the influence gender, age, and the time elapsed from the first dislocation to surgery in the outcomes of Medial Patella Femoral Ligament (MPFL) reconstruction are lacking. This systematic review was conducted to investigate whether patient characteristics have an influence in the clinical outcomes of MPFL reconstruction for patients with patellofemoral instability. Material and methods: This study followed the PRISMA guidelines. The main databases were accessed in February 2021. All the studies reporting outcomes of primary MPFL reconstruction in patients with recurrent patellofemoral instability were considered for inclusion. A multivariate analysis diagnostic tool was used to analyse the association between age, gender and time from injury to surgery and the surgical outcomes at last follow-up. Results: A total of 50 articles (2037 procedures) were included. The mean follow-up was 40.90 ± 24.8 months. The mean age was 23.6 ± 3.9 years. 64.3% (1309 of 2037 patients) were female. The mean time from injury to surgery was 64.5 ± 48.9 months. Women showed no statistically significant association with the Kujala score or complications. Older patients had a reduced risk to incur re-dislocations (P = 0.01) and revisions (P = 0.01). Longer time from injury to surgery was associated with greater risk to incur re-dislocations (P = 0.01), and with lower Kujala score (P < 0.0001). No other statistically significant association was evidenced. Conclusion: The time span from the first patellar dislocation to the surgical reconstruction was a negative prognostic factor, while sex had no influence on surgical outcomes. The role of patients age on surgical outcomes remains unclear.
CRIS-Team Scopus Importer:2022-07-20
Keywords: MPFL reconstruction; Patellofemoral instability; Predictor factors